Pengaruh Motivasi dan Efikasi Diri Terhadap Kinerja Karyawan PT. Golden IB - Yuana Rizki Firdausi; Putu Widhia Rahayu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Employee performance is a strategic factor in supporting the achievement of organizational goals, yet suboptimal performance is still found at PT. Golden IB. This condition is suspected to be influenced by factors such as work motivation and employee self-efficacy. This study aims to analyze the influence of work motivation and self-efficacy on employee performance, both partially and simultaneously. The study used a quantitative approach with a survey method. The study population was all 80 employees of PT. Golden IB, and the sampling technique used saturated sampling to sample the entire population. Data were collected through a questionnaire with a five-point Likert scale and analyzed using multiple linear regression analysis with SPSS. The results showed that work motivation has a positive and significant effect on employee performance, self-efficacy also has a positive and significant effect on employee performance, and work motivation and self-efficacy simultaneously have a significant effect on employee performance at PT. Golden IB. These findings underscore the importance of strengthening employee motivation and self-efficacy as a strategic effort to improve organizational performance..